2021
DOI: 10.15587/1729-4061.2021.242849
|View full text |Cite
|
Sign up to set email alerts
|

Development of a hash algorithm based on cellular automata and chaos theory

Abstract: Information security, reliability of data transfer are today an important component of the globalization of information technology. Therefore, the proposed work is devoted to highlighting the results of the design and development of a hacking-resistant algorithm to ensure the integrity of information transfer via digital technology and computer engineering. To solve such problems, cryptographic hashing functions are used. In particular, elements of deterministic Chaos were introduced into the developed cyclic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Statistical characteristics of generators of pseudorandom sequences, block and stream ciphers based on cellular automata were developed and studied. It is shown that they can be successfully used for cryptographic applications as efficient means of scrambling incoming messages.The developed generators based on the combination of intercellular interaction rules and the original self-developed rule demonstrated good statistical properties and strong avalanche effect 5,6 , which was confirmed by NIST STS tests.…”
Section: Discussionmentioning
confidence: 59%
“…Statistical characteristics of generators of pseudorandom sequences, block and stream ciphers based on cellular automata were developed and studied. It is shown that they can be successfully used for cryptographic applications as efficient means of scrambling incoming messages.The developed generators based on the combination of intercellular interaction rules and the original self-developed rule demonstrated good statistical properties and strong avalanche effect 5,6 , which was confirmed by NIST STS tests.…”
Section: Discussionmentioning
confidence: 59%